ANALISIS INVESTASI DI INDONESIA SUATU PENDEKATAN MODEL DINAMIK - Afrizal, . (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2010)
ABSTRACT The main objective of this article is to analyze econometrically both government and private investment in Indonesia through a dynamic model, particularly Error Correction Model (ECM) in order to examine the validity of empirical  model specification  used in this study. The results of  this study show that estimation of investment rate in Indonesia using ECM during the period 192.1-2007.4 was statistically significant. Partially, real national income has a significantly negative effect on investment rate in Indonesia. This is not in line with exant theory and proposed hypothesis. International interest rate /libor affects significantly on investment, whilst international interest rate /libor in previous period (t-1) is negatively significant on investment. Employment rate growth has a positive relation with investment, but employment rate growth in previous period (t-1) affects significantly negatively on investment in Indonesia.   Keywords : investment model, LIBOR, eror coreection model/ECM